ANALISIS RISIKO FISKAL APBD PROVINSI SULAWESI TENGGARA - Aprialtin, Fildzah; Natsir, M.; Anam, Syamsul (Universitas Halu Oleo, 2023)
The purpose of this study is to identify and analyze fiscal risk factors in the APBD budgeting using quantitative methods. Data obtained from interviews through a questionnaire using the Likert scale method. Respondents in this study consisted of 30 regional civil servants who had been directly involved in the preparation of the APBD budget in Southeast Sulawesi Province, and the analytical tool used in this study was the confirmatory factor analysis (CFA). Based on the results of the analysis in this study, it shows that there are several fiscal risk factors in regional budgeting, namely understanding the risk of risk management, understanding the guidelines for implementing the APBD and adjusting the APBD, KUA and PPAS documents, performance indicators and targets for determining budget allocations